2017
DOI: 10.11149/jkaoh.2017.41.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Oral health literacy of Korean adults

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0/), which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Objectives: We used a questionnaire to measure the oral health literacy of Korean adults. We then evaluated the validity and reliability of the questionnaire. Methods: This questionnaire was developed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…SDM is predicated upon patients’ good understanding of the options/alternatives for treatment and their relative advantages and disadvantages based on the evidence. However, given oral health literacy in Korea was reported to be lower than what would be considered optimal [ 39 ], patients might have difficulty participating in the decision-making process. Other studies outside Korea have also reported that dentists perceived patients’ misconceptions about treatment and treatment outcomes as problematic and an obstacle in decision-making [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SDM is predicated upon patients’ good understanding of the options/alternatives for treatment and their relative advantages and disadvantages based on the evidence. However, given oral health literacy in Korea was reported to be lower than what would be considered optimal [ 39 ], patients might have difficulty participating in the decision-making process. Other studies outside Korea have also reported that dentists perceived patients’ misconceptions about treatment and treatment outcomes as problematic and an obstacle in decision-making [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empathy is measured by ‘cognitive subscales’: (1) Perspective taking (IRI-PT), which measures the tendency to spontaneously adopt the psychological point of view of others, and (2) Fantasy (IRI-FS), which measures the ability to transform oneself into characters of movies, books, plays, etc., and ‘affective aspects’, which can be measured using two affective subscales: (3) Empathic concern (IRI-EC) that measures the ability to assess ‘other'-oriented feelings of sympathy and concern for unhappy others and (4) Personal distress (IRI-PD) that measures “self” oriented feelings of distress and unease in interpersonal settings [ 36 ]. This study used the Korean version of the IRI (K-IRI) translated and validated by Kang et al [ 39 ]. This K-IRI has been used to assess empathy in Korean dental students with the results of appropriate psychometric properties [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Information acquisition and the utilization of dental services might not be directly proportional to educational background. Lee and Chang [ 55 ] reported that approximately 60% of university students had higher oral health literacy than junior high school graduates, but 40% had a lower oral health literacy. Our findings are similar to those reported by Lee and Chang [ 55 ]; however, for the highly educated group, the opportunity cost due to long visit times might be considered as important [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent dental caries, a serious oral disease, removing and controlling dental plaques is the most important 5) . While tooth brushing is the most effective physical method to remove dental plaques 6) , using solely the physical methods such as tooth brushing, dental flossing and interdental brushing, do not ensure the complete removal of dental plaques and it is more effective to use such chemical means as tooth paste and mouth wash in addition to physical methods [7][8][9] . Certain previous studies showed that toothpastes and mouth washes exhibit an antibacterial effect on oral pathogens 10)…”
Section: Introductionmentioning
confidence: 99%